Verbal Bullying di SD Negeri Gendungan: Kajian Kualitatif tentang Dampak Psikososial Siswa - maulid bima; nurratri Kurnia Sari (Tunas Nusantara, 2026)
This study aims to examine the phenomenon of verbal bullying among elementary school students and its psychosocial impacts on victims, particularly their psychological well-being and social interactions. This study employed a qualitative approach using a case study design. The participants consisted of four elementary school students, including two victims and two perpetrators of verbal bullying, with one classroom teacher serving as a supporting informant. Data were collected through participatory observation, in-depth interviews, and documentation, and were analyzed through data reduction, data presentation, and conclusion drawing. The findings revealed five main forms of verbal bullying: negative name-calling, insults and verbal abuse, cruel criticism, false accusations, and verbal threats. Negative name-calling was the most dominant form and was commonly directed at students' physical characteristics and family backgrounds. Verbal bullying occurred both in informal situations, such as during recess, and in formal classroom settings, particularly through harsh criticism of students who experienced academic difficulties. The findings also showed that verbal bullying was often perceived by perpetrators as a form of joking or was imitated from peers. For victims, these behaviors resulted in embarrassment, fear, anxiety, decreased self-confidence, and a tendency to withdraw from social interactions. These findings indicate that verbal bullying is a serious problem in elementary schools that affects students' psychological well-being and the quality of their social interactions. Therefore, preventive efforts involving teachers, schools, and students are needed through stronger supervision, positive communication practices, empathy development, and character education.